2022
DOI: 10.11613/bm.2023.010702
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil-lymphocyte ratio to predict poor prognosis of critical acute myocardial infarction patients

Abstract: Introduction:Inflammation is closely related to adverse outcomes of acute myocardial infarction (AMI). This study aimed to evaluate whether neutrophil-lymphocyte ratio (NLR) can predict poor prognosis of critical AMI patients. Materials and methods:We designed a retrospective cohort study and extracted AMI patients from the "Medical Information Mart for Intensive Care-III" database. The primary outcome was 1-year all-cause mortality. The secondary outcomes were 90-day and in-hospital all-cause mortalities, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…TDROC curves were used to compare the predictive value of the risk stratification based on ln-SIRI and the risk stratification based on optimal cutoffs of NLR ( 10 ) ( Figure 5 and Table 7 ). In the risk stratification based on ln-SIRI, for the 30-day mortality, the AUC is 0.6198, and the Max Youden is 0.2068.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TDROC curves were used to compare the predictive value of the risk stratification based on ln-SIRI and the risk stratification based on optimal cutoffs of NLR ( 10 ) ( Figure 5 and Table 7 ). In the risk stratification based on ln-SIRI, for the 30-day mortality, the AUC is 0.6198, and the Max Youden is 0.2068.…”
Section: Resultsmentioning
confidence: 99%
“…AMI is a formidable global health challenge, accounting for nearly 1.8 million deaths annually and representing a staggering 20% of all mortalities in Europe ( 10 ). Given its high incidence and dire prognosis, AMI poses a grave threat to public health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective study involving 2063 patients with AMI, the incidence and 23 Wang reported that the high and very high neutrophil-lymphocyte ratio groups had a higher risk of AKI incidence (RR = 1.44, 95% CI= 1.06-1.95, P = 0.018 and RR = 1.34, 95% CI= 0.87-2.07, P = 0.180) compared with low-NLR group. 24 Based on these studies, it is reasonable to infer that those inflammatory markers have the potential to predict CRS-I.…”
Section: Discussionmentioning
confidence: 99%